A Synodal Church in the Indian Context of Religious and Cultural Pluralism - Dery Davis K (Asian Horizons, 2025)
This paper is an attempt to illustrate how a synodal Church can walk alongside people from various religions and cultures in India. It explores the theological grounds of religious pluralism, the present-day conditions in India, and how this synodality manifests itself in the religious and cultural pluralistic reality of India. In the multi-religious context of India, synodality is an experience of walking together with people of other faiths and seeking the truth together. The unity within the diversity of the Indian context serves as the foundation for communion and synodality. It helps foster a certain level of religious tolerance. Being a synodal Church entails an ecumenical, participatory, and dialogical interaction with people of different faiths. The paper also focuses on how the synodal principles of communion and participation are used by the Church in the multi-cultural context of India. Finally, it ends with a few suggestions for the future of a synodal Church in India.